High-grade Astrocytoma is Associated with Significant Expression of the Wilms Tumor Gene (WT-1) Protein - Jalbani, Asma; Rahat, Noshaba; Humera Shahzad; Prih Bashir; Farhana Zulfiqar; Zumrud Momin (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To investigate the association between different astrocytoma grades and WT-1gene protein immunoexpression at the Pathology Department of a tertiary care hospital. METHODOLOGY: In this cross-sectional study, sixty biopsies of Astrocytoma were incorporated using non-probability convenience sampling. All cases of various grades of Astrocytoma received in the Department of Pathology, Basic Medical Sciences Institute, JPMC, Karachi, from January 2019 to December 2022, were thoroughly reviewed and included in this research. Biopsy samples with an insufficient amount of material, metastatic Carcinoma and CNS tumors other than Astrocytoma were excluded. Results were analyzed using IBM-SPSS version 23.0. The Pearson Chi-Square test of independence was applied, and P-values less than 0.05 were considered significant. RESULTS: A total of 60 cases of astrocytomas were immunostained for WT-1. Of the 56 samples, 93.3 percent had positive WT-1 cytoplasmic immunostaining. A statistically significant correlation (p < 0.001) was found between the WT-1 score and tumour grade, with low-grade (grades I and II) astrocytomas scoring lower and high-grade (grades III and IV) astrocytomas scoring higher. CONCLUSION: The research confirms WT-1’s role in astrocytoma carcinogenesis and aims to assess its expression across different histological grades. Low expression correlates with lower tumour grades, while high expression indicates higher tumour grades. WT-1 can help distinguish between grades, making it a useful immunohistochemical marker. Its frequent expression in astrocytic tumors supports its potential in immunotherapy, aiding in the identification of candidates for targeted treatment. WT-1 regulates key cellular processes, making it a promising target for improving treatment outcomes in astrocytoma patients.